Formulation of a new flow improver using halba seeds - Abdulbari, Hayder A. (2011)
In this study the effect of adding natural polymer as a drag reducing agent on the pressure drop in pipes carrying aqueous media is studied. A closed loop circulation system is designed to test the efficiency of the natural polymer. The closed loop circulation system is consist of four testing point, transparent PVC pipe up to three meter and 1 inch internal diameter. The natural polymer used in this experiment is mucilage that is extracted from Halba seed. Halba or Fenugreek consists of the dried ripe seeds of a small, southern European herb known technically as Trigonella foenum-graecum L., a member of the family Fabaceae. The seeds contain up to 40 percent of mucilage causing them to be used in various poultices and ointments intended for external application. The efficiency of natural polymer in reducing the percentage of drag is calculated from the data taken from experiment. Different concentration of Halba mucilage is used to test the efficiency of the natural polymer in reducing the drag in pipes. The results shows that the natural polymer extracted from Halba seed can reduce pressure drop in pipes up to 62%. Using natural polymer extracted from plant in reducing drag in pipeline is a great success and has a high commercial value in the future. The advantage of using natural polymer is, they are renewable and environment friendly.